A multiple linear regression analysis on the perception of secondary school students in Tangkak, Johor towards absenteeism / Nornadiah Mohd Razali ...[et al.] - Mohd Razali, Nornadiah; Remy Azrul, Nur Adlina Syazwani; Bahar, Nur Haziera; Mohd Jainuddin, Siti Nur Afifahalin; Paramasivam, Sheela; Abdul Hadi, Az'lina (Unit Penerbitan UiTM Kelantan, 2021)
While school attendance has been one of the determinants of students' success, absenteeism has increased in 2020. This research was conducted to investigate the factors influencing the perception of students towards absenteeism. Additionally, this research aims to compare the perception towards absenteeism between gender as well as between school areas. Factors such as school environment, family problems, student's attitude and health problems were considered in the study. The study involved a total of 580 students who came from two different schools, one represented the urban area and the other represented the rural area. The data were gathered through a questionnaire adapted from a previous study. A multiple linear regression analysis was employed to answer the first objective. The results revealed that the most significant factor that influenced the perception of students towards absenteeism was school environment. For the second objective, an independent z test was employed to compare the perception scores between gender as well as between school area (urban and rural). It was found that the perception of students towards absenteeism differs by gender but did not differ by school area.